1987
DOI: 10.1203/00006450-198711000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Tracheobronchial Mucins from Cystic Fibrosis and Non-Cystic Fibrosis Individuals

Abstract: ABSTRACT. Tracheobronchial mucins from healthy individuals and from patients with bronchial asthma or cystic fibrosis (CF) were isolated from lung mucus, purified, and their chemical and physical properties compared. Normal and asthmatic mucins required both a dissociating and a reducing agent for solubilization and exhibited identical chromatographic behavior on Sepharose 4B, Sepharose 2B, and hydroxylapatite and similar amino acid and carbohydrate compositions. In contrast, 1) C F lung mucins were solubilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…As previously described, MUC5B appeared to be the predominant mucin in CF sputum [12], though this may also reflect more rapid degradation of MUC5AC [21]. Although it has been recognized for some time that bacterial or host inflammatory cell proteases in the sputum may degrade mucins [23], only recently has the importance of such processes begun to be appreciated [24]. As with previous studies [12,13], we also observed a wide range of mucin levels in CF sputum and we have gone on to show that this might represent differences in mucin degradation.…”
Section: Discussionmentioning
confidence: 62%
“…As previously described, MUC5B appeared to be the predominant mucin in CF sputum [12], though this may also reflect more rapid degradation of MUC5AC [21]. Although it has been recognized for some time that bacterial or host inflammatory cell proteases in the sputum may degrade mucins [23], only recently has the importance of such processes begun to be appreciated [24]. As with previous studies [12,13], we also observed a wide range of mucin levels in CF sputum and we have gone on to show that this might represent differences in mucin degradation.…”
Section: Discussionmentioning
confidence: 62%
“…Radiolabeling (metabolic labeling) of mucins also provides information regarding the total release of glycoproteins, as well as the functional state of the secreting cells [128, 129, 137, 140, 145, 146]. When radio-labeled monosaccharides (such as fucose) are used, they can also additional more specific information regarding glycosylation [129, 137].…”
Section: Techniques For Measuring Mucus and Mucinmentioning
confidence: 99%
“…We have reported that in CF sputum, serine proteases degrade mucins after secretion [ 9 ]. Bacterial or host inflammatory cell proteases in CF sputum may further contribute to mucin degradation [ 23 ]. Delayed mucin degradation in COPD could well be caused by this protease-anti protease imbalance.…”
Section: Discussionmentioning
confidence: 99%